The Impact of Gender and Socio-economic Background on Attainment in Scottish State Secondary Schools - Gasteen, Anne (International Journal of Population Data Science, 2019)
Attainment in Scottish Secondary education is characterised by entrenched socio-economic and gender gaps. Pupils from the most deprived 20% of households are significantly less likely to achieve benchmark attainment thresholds set by policymakers in terms of the number of awards gained at different levels. In general, females have outperformed males in secondary education since the 1970s. Subjects studied for formal qualification are important too, not just the number of awards and/or grades. Some subjects carry more weight than others, facilitating entry to more prestigious universities and degree programmes that attract higher labour market premia and social status. This paper used Scottish Qualifications Authority (SQA) administrative data for 2002-2009, linked to the Scottish Index of Multiple Deprivation (SIMD), to investigate the influence of gender and socio-economic background on attainment in so-called facilitating subjects: English, Maths, Geography, History, Modern Studies, Modern Languages, Biology, Chemistry, Physics. Multinomial logit models were estimated for each subject, at each qualification level, to examine within subject attainment in terms of the likelihood of achieving either a low, middle or high pass compared to failing. The impact of socio-economic background was greater than that of gender. Individuals’ relative ability was important for securing low passes but not strong enough to overcome disadvantage to achieve high grades. The effects were particularly stark for age-16 qualifications, with the likelihood of securing any pass grade, in any subject, falling dramatically as disadvantage increased. Socio-economic effects were much reduced at Higher, the crucial qualification for university entry in Scotland, but increased as pass grades rose. Females outperformed males in most subjects at different qualification levels with the notable exceptions of Maths and named sciences at Higher, where males were significantly more likely to pass these at all grades.